Treatment of Atopic Dermatitis with Biologic Drugs - Gabriella Fabbrocini; Maddalena Napolitano; Matteo Megna; Nicola Balato; Cataldo Patruno (Adis, Springer Healthcare, 2018)
Abstract Atopic dermatitis (AD) is a chronic, pruritic, inflammatory skin disease which predominately affects children and usually clears up during infancy or childhood. However, AD may persist with a chronic relapsing course until adulthood or develop at a later age. AD treatment can often be complicated. Treating moderate-to-severe AD can be challenging: only a few therapeutic options are available, with cyclosporine being the only approved and labeled systemic drug. In the last few years, advances in the knowledge of AD pathogenesis have been made that can provide the basis for developing new topical and systemic drugs. Among them, biologic drugs targeting specific cytokines involved in the development of the disease will probably revolutionize AD therapy. Currently, dupilumab, a monoclonal antibody that binds to the shared alpha chain subunit of the receptors for IL-4 and IL-13, is the only biologic drug licensed for the treatment of AD in adults. However, other biologic drugs that selectively target some key cytokines in AD pathogenesis (IL-13, IL-31, and IL-22) are also being studied. In this review, we discuss all of the biologic drugs that have been studied for AD treatment.